The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnut.2022.890942
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization, and Antioxidant Properties of Phycocyanin Complexes Based on Sodium Alginate and Lysozyme

Abstract: In this study, phycocyanin-sodium alginate/lysozyme complex (PC-SLC) was prepared for the first time and characterized by UV spectroscopy, Fourier transform infrared spectroscopy (FT-IR), and circular dichroism spectroscopy (CD). The stability of PC-SLC under light, temperature, pH and simulated gastrointestinal fluid was investigated. The scavenging ability of the complexes against DPPH and ABTS radicals was determined. The results showed that the complex formed by the mass ratio of SA-LZM of 0.1 showed the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
1
0
0
Order By: Relevance
“…In comparison to previous studies 53 , the combined effect of PC and DBD treatment significantly reduces DPPH and ABTS levels, with P 80:5 +PC exhibiting the lowest levels across all days. This observation aligns with previous research on DBD and PC treatments 5 , 54 , 55 . Notably, ascorbic acid oxidation likely contributes to the notable decrease in DPPH observed in all fillets treated at 80 kV starting on the sixth day of storage compared to the control 56 .…”
Section: Discussionsupporting
confidence: 93%
“…In comparison to previous studies 53 , the combined effect of PC and DBD treatment significantly reduces DPPH and ABTS levels, with P 80:5 +PC exhibiting the lowest levels across all days. This observation aligns with previous research on DBD and PC treatments 5 , 54 , 55 . Notably, ascorbic acid oxidation likely contributes to the notable decrease in DPPH observed in all fillets treated at 80 kV starting on the sixth day of storage compared to the control 56 .…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, previous studies demonstrated the ability of alginate-encapsulated C-PC from Spirulina to preserve its antioxidant capacity upon thermal treatment (Qiao et al, 2022). Therefore, encapsulating R-PC or other temperature-sensitive, food-derived PBPs into alginate beads could be an excellent approach to preserve and modulate its techno-functional properties, such as colour, aggregation and antioxidant capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, encapsulating R-PC or other temperature-sensitive, food-derived PBPs into alginate beads could be an excellent approach to preserve and modulate its techno-functional properties, such as colour, aggregation and antioxidant capacity. Furthermore, this approach could be a good strategy for controlling the release of bioactive PBPs in the gastrointestinal tract (GIT) (Qiao et al, 2022). Alginate immobilisation in the presence of calcium ions represents the non-covalent entrapment of the protein of choice by making a gel-like network that surrounds the protein, thus entrapping it within (Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%